Genome-Wide Association Study Identifies Phospholipase C zeta 1 (PLCz1) as a Stallion Fertility Locus in Hanoverian Warmblood Horses - Schrimpf, Rahel (Public Library of Science, 2014)
A consistently high level of stallion fertility plays an economically important role in modern horse breeding. We performed a genome-wide association study for estimated breeding values of the paternal component of the pregnancy rate per estrus cycle (EBV-PAT) in Hanoverian stallions. A total of 228 Hanoverian stallions were genotyped using the Equine SNP50 Beadchip. The most significant association was found on horse chromosome 6 for a single nucleotide polymorphism (SNP) within phospholipase C zeta 1 (PLCz1). In the close neighbourhood to PLCz1 is located CAPZA3 (capping protein (actin filament) muscle Z-line, alpha 3). The gene PLCz1 encodes a protein essential for spermatogenesis and oocyte activation through sperm induced Ca(2+)-oscillation during fertilization. We derived equine gene models for PLCz1 and CAPZA3 based on cDNA and genomic DNA sequences. The equine PLCz1 had four different transcripts of which two contained a premature termination codon. Sequencing all exons and their flanking sequences using genomic DNA samples from 19 Hanoverian stallions revealed 47 polymorphisms within PLCz1 and one SNP within CAPZA3. Validation of these 48 polymorphisms in 237 Hanoverian stallions identified three intronic SNPs within PLCz1 as significantly associated with EBV-PAT. Bioinformatic analysis suggested regulatory effects for these SNPs via transcription factor binding sites or microRNAs. In conclusion, non-coding polymorphisms within PLCz1 were identified as conferring stallion fertility and PLCz1 as candidate locus for male fertility in Hanoverian warmblood. CAPZA3 could be eliminated as candidate gene for fertility in Hanoverian stallions.